(untitled) (Biological Sciences - PJSIR, 2021)
Food security is a serious issue in developing countries like Pakistan because of ever-increasing population. To feed the hunger population, safe and nutritious vegetables are growing concern as they are being polluted by heavy metals. The present study was conducted to investigate the concentration of heavy metals such as cadmium (Cd), chromium (Cr), lead (Pb), nickel (Ni), iron (Fe), manganese (Mn), and zinc (Zn) in highly consumed vegetable collected from peri-urban markets of Rawalpindi and Multan region. Health risk associated with the consumption of these vegetables in term of estimated daily intake of metals (EDIM) and health risk index (HRI) was also evaluated among local consumers. Results showed that mean values of cadmium (Cd), and lead (Pb) in all vegetable samples from both region were exceeding the respective MAL set by FAO/WHO. Estimated daily intake of heavy metals was found below than the permissible limit. EDIM showed following decreasing trend Fe > Zn > Mn > Ni > Pb > Cr and Cd, respectively. The health risk index (HRI) for all heavy metals were less than the threshold level (1), indicating no significant threat to the local population through the consumption of these vegetables.